Legal Reconstruction of the Notary Supervision Mechanism in Preventing Document Forgery as a Basis for Making Authentic Deeds in Indonesia - Kartika; Zainal Arifin Hoesein (SULTAN ADAM: Jurnal Hukum dan Sosial, 2026)
This study aims to analyze the legal framework governing the notary supervision mechanism in preventing document forgery as the basis for the preparation of authentic deeds in Indonesia, identify legal weaknesses in the current supervision system, and formulate a legal framework capable of ensuring legal certainty. The study employs a normative legal methodology using both a statutory and a conceptual approach. The findings reveal that notary supervision is regulated under Law No. 2 of 2014 on the Office of the Notary through the Supervisory Board and the Notary Honorary Board; however, it has not yet been able to effectively prevent the use of forged documents in the preparation of authentic deeds. These weaknesses include a lack of regulations regarding legal due diligence, unclear obligations regarding document verification, the absence of national standards for document authenticity checks, limited notary access to government databases, and a supervisory system that remains repressive in nature. The proposed legal reforms include strengthening identity and document verification requirements, regulating notary legal due diligence, integrating the notary system with the national database, developing an electronic verification system, implementing an early warning system, and establishing a cyber notary supervision model. These reforms are expected to strengthen legal certainty, legal protection, and the effectiveness of notary supervision in the face of digital technology advancements and the increasing number of document forgery cases.